(untitled) (Journal of history, 2023)
The article aims to highlight the prerequisites for organizing expeditions of the Italian travelers Plano Carpini and Marco Polo to Central Asia. Also, the purpose of the study is a general description of the historical notes of Italian travelers and their scientific value. The tasks, results and features of the travels of Marco Polo, Ricoldo da Montecroce and Plano Carpini are analyzed and rethought. The theme of travel from Europe to Asia in the Middle Ages is still relevant and of interest. In Italy, in the 13th century, many prerequisites for organizing expeditions were established, and the expeditions themselves solved important research and socio-political problems. The purpose of this article is to study the expeditions of Italian travelers to Central Asia in the XIII century. The following tasks are set: - to study the prerequisites for organizing expeditions; - analyze the routes of Marco Polo, Ricoldo da Montecroce and Plano Carpini; - describe the features of the preparation and conduct of expeditions in the XIII century; - to identify the scientific value of expeditions. The object of the study is the historical process in Europe in the XIII century in the context of the study of new territories. The subject of the study is the travels of Marco Polo, Ricoldo da Montecroce and Giovanni de Plano Carpini to Central Asia. Keywords: Central Asia, the Middle Ages, Italian travelers, Plano Carpini, Marco Polo, Ricoldo da Montecroce